2023
DOI: 10.3390/plants12213758
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Harvest Dates for Three Major Cultivars of Blue Honeysuckle (Lonicera caerulea L.) in China

Min Yu,
Songlin Li,
Ying Zhan
et al.

Abstract: Blue honeysuckle (Lonicera caerulea L.) is an emerging fruit crop; however, determining its proper harvest time in commercial cultivation remains challenging due to its rapid fruit development characteristics. In this study, we investigated 17 agronomic traits of three blue honeysuckle cultivars harvested on 5 successive dates within their respective harvest windows. ‘Lanjingling’, ‘Wulan’, and ‘Berel’ showed solid–acid ratios (SS:TA) ranging from 10.00 to 16.01, 8.13 to 10.23, and 5.77 to 7.11, respectively; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…However, there was an unexpected peak in a* value at 50 • C, which could be attributed to the complete loss of cuticular wax at this specific temperature or drying time. Moreover, compared with fresh blue honeysuckle berries [1,3], the dried blue honeysuckle berries showed no remarkable enhancement of SS/TA ratio, and relative to other dried small berries [18], the dried blue honeysuckle berries showed a relatively low level value of SS/TA ratio (~10). These results suggested that further dehydration-based processing of blue honeysuckle berry should involve sugaring.…”
Section: Color and Basic Qualitymentioning
confidence: 81%
See 3 more Smart Citations
“…However, there was an unexpected peak in a* value at 50 • C, which could be attributed to the complete loss of cuticular wax at this specific temperature or drying time. Moreover, compared with fresh blue honeysuckle berries [1,3], the dried blue honeysuckle berries showed no remarkable enhancement of SS/TA ratio, and relative to other dried small berries [18], the dried blue honeysuckle berries showed a relatively low level value of SS/TA ratio (~10). These results suggested that further dehydration-based processing of blue honeysuckle berry should involve sugaring.…”
Section: Color and Basic Qualitymentioning
confidence: 81%
“…The plants were cultivated for six years at the Experimental Farm of Northeast Agricultural University (NEAU) in Xiangyang town, Harbin, China (E 126 • 56 ′ 2 ′′ , N 45 • 46 ′ 10 ′′ ). On reaching commercial maturity (SS: TA ≥ 8) [3], the fruits were manually harvested and immediately subjected to a rapid field-heat removal process by the blowing of ambient air at room temperature (~20 • C) in the dark for 30 min. To minimize the removal of cuticular wax, no specific surface cleaning or washing procedures were performed.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations